2017
DOI: 10.1371/journal.pntd.0005798
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of enteroaggregative Escherichia coli infections and associated outcomes in the MAL-ED birth cohort

Abstract: BackgroundEnteroaggregative E. coli (EAEC) have been associated with mildly inflammatory diarrhea in outbreaks and in travelers and have been increasingly recognized as enteric pathogens in young children with and without overt diarrhea. We examined the risk factors for EAEC infections and their associations with environmental enteropathy biomarkers and growth outcomes over the first two years of life in eight low-resource settings of the MAL-ED study.MethodsEAEC infections were detected by PCR gene probes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 59 publications
8
64
0
2
Order By: Relevance
“…These pathotypes are known agents of traveller's diarrhoea [71,72]. Though they are frequently isolated in asymptomatic cases, reports have shown that even in the absence of diarrhoea, they are associated with intestinal inflammation, which may impact child's development [73]. In developing countries, the prevalence of EAEC pathotypes among diarrhoea cases ranges from 4.5% to 41% [69,71,74,75].…”
Section: Prevalence Of Dec Pathotypesmentioning
confidence: 99%
“…These pathotypes are known agents of traveller's diarrhoea [71,72]. Though they are frequently isolated in asymptomatic cases, reports have shown that even in the absence of diarrhoea, they are associated with intestinal inflammation, which may impact child's development [73]. In developing countries, the prevalence of EAEC pathotypes among diarrhoea cases ranges from 4.5% to 41% [69,71,74,75].…”
Section: Prevalence Of Dec Pathotypesmentioning
confidence: 99%
“…However, some strains have acquired pathogenic potentials allowing them to cause diarrhoea (intestinal pathotypes) and other systemic illnesses involving the urinary tract, brain and blood (extra intestinal pathotypes) 1 . Intestinal or diarrhoeagenic E. coli (DEC) strains constitute the primary diarrhoea aetiologic agents in children younger than five years old 2,3 and in most cases, they are associated with growth defects 4 . About 760,000 children lose their lives every year to diarrhoeal diseases worldwide 5 .…”
Section: Introductionmentioning
confidence: 99%
“…EAEC members have been reported to cause inflammation of the intestines in children and impairing their growth and negatively impacting their development even without diarrhoea 4 . EAEC virulence genes are heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El patotipo EAEC fue hallado en niños con cuadros agudos, prolongados y persistentes. La presencia de este patógeno en niños con diarrea del cuadro está en coincidencia con numerosas investigaciones (Nguyen et al, 2006;Al-Gallas et al, 2007;Okeke et al, 2009;Jafari et al, 2009;Rajendran et al, 2010;Kaur et al, 2010;Kermani et al, 2010;Croxen et al, 2013;Hebbelstrup Jensen et al, 2014;Tobías et al, 2015;Tian et al, 2016;Schilling et al, 2017;Rogawski et al, 2017).…”
Section: Discussionunclassified